Tinjauan Atas Content Marketing PT Pojok Satu Indonesia - Widjaya, Mutiara Malika; Setiawan, Budi (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Before technology experienced developments like today, to find information and news, people got it through conventional media including newspapers, magazines, radio or television. The conventional media industry such as newspapers began to lag behind due to the impact of technological developments, this was due to changes in people's behavior that switched to the digital world. The objectives of this study are: 1) how is content marketing implemented at PT Pojok Satu Indonesia; 2) what are the obstacles in implementing content marketing at PT Pojok Satu Indonesia; 3) how to deal with obstacles in implementing content marketing at PT Pojok Satu Indonesia. The results of this study are: 1) PT Pojok Satu Indonesia divides three stages in implementing content marketing; 2) in its implementation there are several obstacles experienced by PT Pojok Satu Indonesia in implementing content marketing including the absence of the right idea in determining a concept that suits the needs of the audience, writer's block, the presence of competitors, and rapidly changing trends; 3) efforts made to overcome obstacles in implementing content marketing at PT Pojok Satu Indonesia, namely identifying target audiences by conducting market research first, dealing with situations when writer's block occurs by taking a break, looking for a new atmosphere and looking at other references, providing characteristics to digital content created by the company and developing a mindset or way of thinking to carry out various innovations. Keywords: Content Marketing, PT Pojok Satu Indonesia